TERMIN DO UZUPEŁNIENIA NALEŻNEJ OPŁATY PRZEZ PROFESJONALNEGO PEŁNOMOCNIKA W RAZIE WNIESIENIA ZAŻALENIA NA ZARZĄDZENIE O ZWROCIE POZWU - Jędrejek, Grzegorz (Zeszyty Prawnicze, 2016)
THE TERM IN WHICH A PROFESSIONAL PROXY MUST MAKE THE REQUIRED PAYMENT FOR AN APPEAL AGAINST A RULING DISMISSING PROCEEDINGS Summary The aim of this paper is to answer the question whether the provisions of Art. 1302 § 2 of the Polish Civil Proceedings Code (k.p.c.) are applicable in the event of an appeal against a ruling to dismiss a case on grounds of non-payment of the court fee. Doubts have been raised on the admissibility of payment by a professional attorney within a term of seven days of the service of a court’s decision to dismiss a case. Under Art. 1302 § 2 k.p.c. the legislator has allowed for payment of the court fee due within a term of one week from the day on which notice is served on the court’s decision to dismiss the case. The position of the author of this paper is that the term of seven days provided for the remittance of the court fee due in the event of an appeal, as defined in Art. 1302 § 2 k.p.c., starts on the day notice is served on the court’s decision to dismiss a case. Any other position on the matter would be in breach of the legal principles at the root of an individual’s right of access to the law and his right to appeal, as guaranteed by the Constitution of the Republic of Poland, as well as in breach of the prohibition of reformationis in peius. The lodging of an appeal cannot lead to the dismissal of the civil recovery proceedings defined in Art. 1302 § 2 k.p.c.